PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI, DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN - Zainul Arifin Noor (EKUITAS (Jurnal Ekonomi dan Keuangan), 2012)
This research aims to test and prove the influence of organizational culture, organizational commitment, and motivation of work towards job satisfaction and performance of employees of PT Indofood Sukses Makmur Tbk Kalimantan. The population in this study were employees of PT Indofood Sukses Makmur Tbk Kalimantan some 392 employees originating from the manufacturing, human resources development, marketing, and accounting. Using the formula, the respondent elected slovin as samples of 50.5% of the number of 198 employees originating from the manufacturing of 155 employees, human resources a number of 19 employees, marketing a number of 14 employees, and accounting of 10 employees. Based on the results of data analysis using Structural Equation Modeling (SEM) through AMOS 16.0, the results showed the 7 proposed hypotheses, there is a significant hypothesis 6 or received and there is a rejected hypothesis 1. As for the hypothesis is a hypothesis accepted: 1. Organizational culture affect significantly to job satisfaction of employees. Hypothesis 2. Organizational commitment affect significantly to job satisfaction of employees, the hypothesis 3. Influential work motivation significantly to job satisfaction of employees, hypothesis 4. Organizational culture affect significantly the performance of employees, the hypothesis 6. Significant impact on the motivation of working performance of employees, and hypotheses 7. Job satisfaction influence significantly the performance of the employees of PT Indofood Sukses Makmur Tbk Kalimantan. The hypothesis was rejected while the 1 is the hypothesis that 5 has no effect on the Organization's commitment to the performance of the employees of PT Indofood Sukses Makmur Tbk Kalimantan